Malignancy Risk and Related Factors of Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance in Thyroid Fine Needle Aspiration - So-hyeon Hong; Hyejin Lee; Min-Sun Cho; Jee Eun Lee; Yeon-Ah Sung; Young Sun Hong (International Journal of Endocrinology)
Atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) in thyroid fine needle aspiration (FNA) is a challenging category. The malignancy risk is different by multiple factors and subsequent management strategy is inconclusive. Therefore, we analyzed the malignancy risk of AUS/FLUS according to radiological and clinical features. A total of 687 nodules that had been initially diagnosed as AUS/FLUS were retrospectively reviewed from 6365 thyroid FNAs between 2011 and 2014. The ultrasonographic (US) features were categorized using the Korean Thyroid Imaging Reporting and Data System. Radiological and clinical features were compared according to the second FNA results or histologically confirmed results from surgery. Repeat FNA was performed on 248 (36%) nodules, and 49 (7%) nodules underwent immediate surgery. Among the 248 nodules subjected to repeated FNA, 49 (20%) nodules were diagnosed again as AUS/FLUS, 123 (50%) were found to be benign, and 47 (19%) were diagnosed as follicular neoplasm, suspicious for malignancy or malignant. Among histologically confirmed nodules, the US features were more unfavorable in malignant nodules, and hypo- or anechogenicity was associated with a higher risk of malignancy after adjusting for age, size, and other US features (P<0.01). In conclusion, we observed that malignant nodules tended to show unfavorable US features, especially hypo- or anechogenicity. Age, sex, and thyroid function were not significantly associated with malignancy risk. We also found out that malignancy risk was not different between the group which underwent immediate operation following the AUS/FLUS diagnosis and the group which underwent repeated FNA after the initial diagnosis.